FUNCraft: Pengembangan Kreativitas dan Motorik Halus Anak Melalui Kerajinan Tangan - Subar Junanto; Sukma Wisnu Pamungkas; Aryn Widawati; Rifda Syafiqoh Nur’aini; Layla Dzurriyyatur Rohmah (Arfah BHMS Foundation, 2025)
Creativity and fine motor skills are crucial aspects of development in elementary school-aged children. The community service program entitled Funcraft in Serenan Village, Juwiring District, Klaten Regency, aims to develop children's creativity and fine motor skills through crafting activities using simple and recycled materials. The activity was attended by 45 children aged 6–13 years and was held over two days during the second week of KKN. Results showed that around 85% of children were able to make crafts independently, and 70% demonstrated high creativity by creating variations of crafts beyond the examples given. This program also had a positive impact in reducing gadget use, fostering environmental awareness, and strengthening emotional bonds between students and the community. Funcraft is a strategic step in supporting the realization of child- and women-friendly villages. Keywords: Funcraft, creativity, fine motor skills, community service, children